5 - The Impact of Gender and Residential Background on Racial Integration: Evidence from a South African University - Josephine Morolake Adeagbo, (African Sociological Review, 2018)
South Africa is one of those countries that openly rejected racism and this is entrenched in its Bill of rights. Despite the acceptance and incorporation of racial integration into the South Africa Constitution, the implementation within some sectors, most especially the educational sector, seems difficult. Recent occurrences of racism in some higher institutions of learning in South Africa are indications that racial integration/ racial transformation is still farfetched in the country’s higher educational sector.It is against this background that this study was conducted to understand how gender and residential background influence racial integration in a South African university which was predominantly a white Afrikaner institution.Using a quantitative method to test the attitude of different categories of undergraduate students at theuniversity, this study found that the factors- residential background and gender- used in measuring student’s attitude do not necessarily have a significant relationship towards racial integration. However, this study concludes with a call for more research with a range of other factors in order to better understand how racial integration can be promoted in South African institutions of higher learning